PENGARUH PENGUNGKAPAN EMISI KARBON DAN MFCA TERHADAP KINERJA KEUANGAN DENGAN MODAL INTELEKTUAL SEBAGAI MODERASI - Sugeng Hariadi; Fitria Rahmawati (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the impact of carbon emission disclosure and Material Flow Cost Accounting (MFCA) on financial performance, with intellectual capital as a moderating variable, for transportation equipment industry companies listed on the Tokyo Stock Exchange during 2021-2023. Using purposive sampling, 27 companies were selected, resulting in 81 observations over three years. The research adopts a causal, quantitative approach, with data sourced from financial and sustainability reports. Analysis included descriptive statistics, classical assumption testing, and hypothesis testing (Coefficient of Determination, t-test, multiple linear regression, and moderated regression analysis). The findings indicate that carbon emission disclosure significantly affects financial performance, while MFCA does not have a significant effect. However, intellectual capital moderates the relationship between carbon emission disclosure and MFCA on financial performance.